2020
DOI: 10.1186/s12967-020-02256-5
|View full text |Cite
|
Sign up to set email alerts
|

The permissive role of TCTP in PM2.5/NNK-induced epithelial–mesenchymal transition in lung cells

Abstract: Background: Translationally controlled tumor protein (TCTP) is linked to lung cancer. However, upon lung cancer carcinogens stimulation, there were no reports on the relationship between TCTP and lung cell carcinogenic epithelial-mesenchymal transition (EMT). This study was designed to investigate the molecular mechanism of regulation of TCTP expression and its role in lung carcinogens-induced EMT. Methods:To study the role of TCTP in lung carcinogens [particulate matter 2.5 (PM 2.5 ) or 4-methylnitrosamino-l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Using the same cell line, it was further confirmed that TCTP promotes EMT and tumorigenicity [90,91] by influencing the expression levels of key transcription factors (ZEB1 and alpha SMA), and of miR-200a, miR-141, and miR-424 [90]. A very recent study also showed that TCTP is a key mediator in the induction of EMT by cigarette smoke carcinogens in lung epithelial and non-small-cell lung cancer cells [70]. Overall, these recent reports on the essential role of TCTP in EMT generated substantial support for our original observation [77] that decreased cellular levels of TCTP in cancer cells inhibit tumorigenicity by interfering with migration and invasion.…”
Section: Mechanisms Of Cancer Promotion By Tctpmentioning
confidence: 72%
See 1 more Smart Citation
“…Using the same cell line, it was further confirmed that TCTP promotes EMT and tumorigenicity [90,91] by influencing the expression levels of key transcription factors (ZEB1 and alpha SMA), and of miR-200a, miR-141, and miR-424 [90]. A very recent study also showed that TCTP is a key mediator in the induction of EMT by cigarette smoke carcinogens in lung epithelial and non-small-cell lung cancer cells [70]. Overall, these recent reports on the essential role of TCTP in EMT generated substantial support for our original observation [77] that decreased cellular levels of TCTP in cancer cells inhibit tumorigenicity by interfering with migration and invasion.…”
Section: Mechanisms Of Cancer Promotion By Tctpmentioning
confidence: 72%
“…In the latter case, the authors observed that miR-27b levels were significantly reduced in tumor tissue of oral cancer patients, resulting in an increase of TCTP protein expression. Similarly, two recent papers reported on the deregulated TCTP expression in cancer, due to low levels of certain miRNAs, i.e., miR-145-5p in prolactinoma [69] and miR-125-3p in lung cancer [70]. In the latter paper, the authors studied the induction of TCTP in lung cells by tobacco smoke carcinogens.…”
Section: Translational Regulationmentioning
confidence: 93%
“…And more, NNK and its metabolites in the lung cell could activate some targets, such as TCTP, 15-LOXs PPARγ, and HO-1, to promote lung cell carcinogenesis. 25 , 26 , 31 , 35 Obviously, the signaling events induced by NNK through α7nAChR-CD36 have a significant contribution to the carcinogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed according to the procedure of ABC-HRP kit (Vector Laboratories, Burlinegame, CA) and protein expression levels were scored 1 to 12 according to the IRS method. 35 , 51 The immunoreactive score (IRS) was calculated as intensity of the staining reaction multiplied by the percentage of positive cells. IF was performed as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Vimentin antibody (46173) was purchased from Cell Signaling (Boston, MA). Protein expression levels were scored as previous description [ 51 , 52 ]. 5 μm paraffin sections of the tissues were stained with haematoxylin-eosin for 3–5 min.…”
Section: Methodsmentioning
confidence: 99%